Optimizing Loan Approval Processes with Support Vector Machines (SVM) - Novita Angraini; Kelly Rosalina; Andini Kosasih (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
Loan approval is a critical process in banking, requiring accurate assessment of borrower risk to minimize defaults while maintaining customer satisfaction. This study explores the optimization of loan approval processes using Support Vector Machines (SVM), a robust machine learning method known for its effectiveness in classification tasks. We utilized a dataset comprising historical loan applications, incorporating features such as credit score, income level, debt-to-income ratio, and employment history. The SVM model was trained and evaluated using cross-validation techniques to ensure generalizability. Our results demonstrate that SVM outperforms traditional statistical methods in predicting loan approval decisions, achieving higher accuracy and a significant reduction in false positives. Furthermore, feature importance analysis revealed that credit score and debt-to-income ratio are the most influential factors in the model's decision-making process. By integrating the optimized SVM model into existing banking workflows, institutions can streamline their approval processes, reduce operational costs, and improve customer experience. This study highlights the potential of SVM in modernizing decision-making frameworks in the banking sector, paving the way for further adoption of advanced machine learning techniques in financial services.